023 Impact of pandemic on neurologists and neurology practice. Issue 9 (12th August 2022) - Kipps, Christopher; Mummery, Catherine
Abstract : Background: Prior to the pandemic, a significant number of neurologists were experiencing levels of burnout in one or more factors as measured using the Maaslich Burnout Inventory (emotional exhaustion, depersonalisation, lack of personal accomplishment). Early in the pandemic, repeat assessment showed marked improvement in Maaslich scores (Spring 2020). We aimed to identify the impact of changes to neurology work practice on neurologists in the prolonged pandemic period. Methods: Working ABN members were surveyed in Autumn 2021 using the Maaslich inventory and questions on work practice. Results: We received 360 responses (n=296 Maaslich). Endorsement of burnout factors had returned to pre-pandemic levels (Spring 2020 less than pre-pandemic/Autumn 2021 t=5.426, P<0.001). Emotional Exhaustion correlated with service waiting times and individual fatigue, and inversely to QoL. Deperson- alisation correlated with fatigue and perceived reduction in service quality (inpatients). Most neurologists felt that inpatient (57%) and outpatient (77%) care quality had declined. Capacity in services remained constrained – less than 75% pre-pandemic capacity for MRI (23.3%), CSF sampling (32.8%) and neurophysi- ology (34.5%). Ability to attend educational events correlated with perceived service quality levels. Satis- faction and confidence in remote assessments was consistently lower than for face-to-face interaction. Conclusion: The pandemic has had a marked effect on neurologists, their QoL and their practice. Levels of burnout correlate with personal fatigue and clinical service quality. Interestingly recent burnout scores are similar to those seen prior to the pandemic.